Salivary testosterone measurement by liquid chromatography tandem mass spectrometry in adult males and females. (May 2014) - Keevil, BG; MacDonald, P; Macdowall, W; Lee, DM; Wu, FCW; ,
Background: Salivary testosterone (Sal-T) may be a useful surrogate of serum free testosterone. The study aims were to use a novel liquid chromatography tandem mass spectrometry (LC-MS/MS) assay to determine whether Sal-T concentrations accurately reflect Sal-T concentrations in both sexes and to investigate practical aspects of sample collection. Methods: Saliva and serum samples were collected in 104 male and 91 female subjects. A more sensitive LC-MS/MS assay was developed to enable Sal-T quantitation in the low concentrations found in females. Saliva (200 µL) was extracted with 1 mL of methyl- tert -butyl ether following the addition of D5-testosterone. Quantitation was performed using a Waters TQ-S mass spectrometer. Results: The assay achieved a lower limit of quantification of 5 pmol/L, sufficiently sensitive to measure testosterone in female saliva. Sal-T showed a diurnal variation but samples taken at weekly and monthly intervals showed no significant differences. Sal-T was stable at ambient temperature for up to 5 days, after freeze-thawing and 3 years frozen storage. Reference intervals for Sal-T were 93–378 pmol/L in males and 5–46 pmol/L in females. Sal-T correlated significantly with serum calculated free-T in males ( r = 0.71, P < 0.001) and in females ( r = 0.39, P < 0.001). Conclusions: These results confirm that testosterone can be reliably and accurately measured by LC-MS/MS in both adult male and female saliva samples. These results lay the foundation for further exploration of the clinical application of Sal- T as a reliable alternative to serum testosterone in the diagnosis and management of androgen disorders and assessment of androgen status in clinical research.